Vodnik, Prešeren in začetki postavljanja spominskih obeležij slovenske literarne kulture - Dović, Marijan (Primerjalna književnost, 2013)
The surprising spread of memorial landmarks of Slovenian literary culture, proven by current empirical research, raises several questions, including that of the historical origins and motivations of such landmarks. This article demonstrates their close connection to the canonization of two key figures of Slovenian poetry from the early nineteenth century, Valentin Vodnik and France Prešeren, and to the installation of their statues in Ljubljana's public space in 1889 and 1905.
Keywords: Prešeren, France, 1800-1849; Vodnik, Valentin, 1758-1819; literatura in prostor; Slovene literature; slovenska književnost; slovenska kultura; kulturni spomin; nacionalna identiteta; kulturni svetniki; spomeniki